PENINGKATAN PENGETAHUAN GIZI SEIMBANG DAN MITOS SEPUTAR GIZI PADA KELUARGA PRA-SEJAHTERA DI KELURAHAN DELIMA PEKANBARU - Alsukri, Saipul; Syuryadi, Novfitri; Ernalia, Yanti (Universitas Muhammadiyah Tapanuli Selatan, 2020)
The wrong dietary pattern will cause various diseases. Health and nutrition counseling is one of a variety of ways to improve knowledge. The advice can improve nutrition knowledge to mothers, which is will impact on changing the nutritional food their family members, including their toddlers. This community service carried out at Kelurahan Delima, Kecamatan Tampan, Pekanbaru. The mother's decision as a participant partner in this service was because she was a family member who prepared food for their family. This community service activity carried out with counseling methods by leaflets, demonstrations, and assessments with anthropometric methods. Other than that, a pre-test and post-test evaluation carried out to understanding balanced nutrition by them. This activity can improve their knowledge about a balanced diet, the results of the post-test partners evidence this.